The role of stretching in tendon injuries. Issue 4 (29th January 2007) - Witvrouw, E; Mahieu, N; Roosen, P; McNair, P
Abstract : The function of tendons can be classified into two categories: tensile force transmission, and storage and release of elastic energy during locomotion. The action of tendons in storing and releasing energy is mainly seen in sports activities with stretch-shortening cycles (SSCs). The more intense the SSC movements are (jumping-like activities), the more frequently tendon problems are observed. High SSC movements impose high loads on tendons. Consequently, tendons that frequently deal with high SSC motion require a high energy-absorbing capacity to store and release this large amount of elastic energy. As the elasticity of tendon structures is a leading factor in the amount of stored energy, prevention and rehabilitation programmes for tendon injuries should focus on increasing this tendon elasticity in athletes performing high SSC movements. Recently, it has been shown that ballistic stretching can significantly increase tendon elasticity. These findings have important clinical implications for treatment and prevention of tendon injuries.